2021
DOI: 10.1007/s12223-021-00889-7
|View full text |Cite
|
Sign up to set email alerts
|

War of the microbial world: Acanthamoeba spp. interactions with microorganisms

Abstract: Acanthamoeba is known to interact with a plethora of microorganisms such as bacteria, fungi and viruses. In these interactions, the amoebae can be predatory in nature, transmission vehicle or an incubator. Amoebae consume microorganisms, especially bacteria, as food source to fulfil their nutritional needs by taking up bacteria through phagocytosis and lysing them in phagolysosomes and hence play an eminent role in the regulation of bacterial density in the nature and accountable for eradication of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 114 publications
1
15
0
Order By: Relevance
“…Whether the astA gene identified in the ECORI strain was derived from another E. coli strain simultaneously present in the Acanthamoeba or acquired in another different way, remains to be ascertained. Whatever the mechanism was, however, our findings suggest that the acquisition of exogenous genes by bacteria during their permanence into Acanthamoeba is possible and strengthen the role of this amoeba as a gene melting pot (Mungroo et al, 2021). In conclusion, our findings showed that E. coli, including STEC, can survive inside protozoan for extended periods of time.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Whether the astA gene identified in the ECORI strain was derived from another E. coli strain simultaneously present in the Acanthamoeba or acquired in another different way, remains to be ascertained. Whatever the mechanism was, however, our findings suggest that the acquisition of exogenous genes by bacteria during their permanence into Acanthamoeba is possible and strengthen the role of this amoeba as a gene melting pot (Mungroo et al, 2021). In conclusion, our findings showed that E. coli, including STEC, can survive inside protozoan for extended periods of time.…”
Section: Discussionsupporting
confidence: 66%
“…was evidenced for STEC but also for the non-pathogenic commensal E. coli strain (ECORI). There are no reports describing this condition, however a non-invasive E. coli K-12 strain has been shown to be present intracellularly in amoebas, even if, after a short time it was lysed by amoebas, indicating E. coli K-12 as bacterial prey rather than an endosymbiont (Mungroo et al, 2021). We hypothesize that the strain used in this study, being a commensal in human intestine, may have acquired mechanisms allowing it to resist within the free-living amoebae.…”
Section: Discussionmentioning
confidence: 79%
“…A previous study by Mungroo et al . [ 44 ] demonstrated that the Acanthamoeba -bacteria co-operative relationship improved Acanthamoeba survival.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that at 20°C, the protozoa thrived, while the bacteria including coliforms were being preyed by the thriving protozoa ( Bott and Kaplan, 1990 ). Most bacteria and some coliforms are digested as a food source, while most coliforms are able to resist lysosomal attack and therefore multiplied within membrane-bound vacuoles ( Barker et al, 1999 ; Van Elsas et al, 2011 ; George et al, 2020 ; Mungroo et al, 2021 ). Previous studies have noted that protozoa, such as Acanthamoeba, can inhibit bacterial growth through the release of free radicals in their lysates ( Connor et al, 1993 ), but have no inhibitory effect on certain coliforms, such as E. coli .…”
Section: Discussionmentioning
confidence: 99%